Zonasi Daerah Pantai Berdasarkan Populasi Foraminifera Muda : Studi Kasus Teluk Banyuwangi - Agus Supangat (Jurnal Matematika & Sains, 1998)
The total population off forminifera found in Banyuwangi Bay is 53 spesies. It consists of 3 types : 64,4% hyaline type, 22,6% porcelaine type, and 13,2% agglotine type. The density ranges between 17000 - 38000 individu per 50 cm3 sediment. Based on Fisher diversity index this area is divided into three regions. Species that are predominantly found in Banyuwangi Bay are Ammonia tepida, Bolivina striatula, Haynesina germanica, Elphidium advenum, Quinqueloculina seminula, Reusella aculeata, Pararotalia sp and Miliammina spp. The results of the factorial analysis test based on station and its species show that there are three zonations in the Banyuwangi Bay. The first zone is influenced by the Java Sea, the second zone is influenced by shrimp pond wastes, and the third zone by the mangrove.